PENGGUNAAN ALGORITMA CLUSTERING K-MEANS UNTUK MENGELOMPOKKAN POLA CUACA - Ilham Rinaldi; Harmayani Harmayani (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2025)
Abstract: Weather pattern analysis is crucial for enhancing disaster preparedness and mitigation in Indonesia, particularly in the face of climate change and extreme weather conditions. This study applies the K-Means algorithm to cluster daily weather data obtained from the Meteorology, Climatology, and Geophysical Agency (BMKG). Using average temperature (Tavg) and average humidity (RH_avg) as variables, the data were analyzed to identify two primary weather patterns: "rainy weather" and "cool humid weather." The clustering results are visualized in a web-based application designed to facilitate interpretation for the general public. The implementation of the K-Means algorithm in this application provides clearer insights into daily weather variations and has the potential to support planning and disaster mitigation in Indonesia. Keywords: Weather, K-Means, weather patterns, disaster mitigation, web-based                  application. Abstrak: Analisis pola cuaca sangat penting untuk mendukung kesiapsiagaan dan mitigasi bencana di Indonesia, terutama dalam menghadapi perubahan iklim dan cuaca ekstrem. Penelitian ini menerapkan algoritma K- means untuk mengelompokkan data cuaca harian yang diperoleh dari Badan Meteorologi, Klimatologi, dan Geofisika (BMKG). Dengan menggunakan variabel suhu rata-rata (Tavg) dan kelembapan rata-rata (RH_avg), data dianalisis untuk mengidentifikasi dua pola cuaca utama: ‘cuaca hujan’ dan ‘cuaca dingin lembab’. Hasil pengelompokan ini divisualisasikan dalam aplikasi berbasis web yang dirancang untuk mempermudah interpretasi bagi masyarakat umum. Implementasi algoritma K-means dalam aplikasi ini memberikan gambaran yang lebih jelas mengenai cuaca harian, serta berpotensi mendukung perencanaan dan mitigasi bencana di Indonesia. Kata kunci: Cuaca, K-means, pola cuaca, mitigasi bencana, aplikasi berbasis web.